2017
DOI: 10.1001/jamadermatol.2016.5861
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Demographic and Photobiological Features of Chronic Actinic Dermatitis in Patients With Lighter vs Darker Skin Types

Abstract: Are there differences in demographic and photobiological features between people of darker and lighter skin types with chronic actinic dermatitis (CAD)?Findings: Retrospective review found darker skin type patients with CAD present at a younger age and with reversed sex ratio compared to lighter skin type patients, although phototest reactions are equally severe. Photopatch reactions are also commonly seen in patients with CAD.Meaning: In contrast to what is classically known about CAD, darker skin type patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
3
19
1
Order By: Relevance
“…found that the majority of outpatients had reduced MEDs in broad spectra, mainly UV‐B and partly UV‐A, with visible ray in the minority. This fact was corroborated by other studies in Korea, Greece, Australia, and the USA …”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…found that the majority of outpatients had reduced MEDs in broad spectra, mainly UV‐B and partly UV‐A, with visible ray in the minority. This fact was corroborated by other studies in Korea, Greece, Australia, and the USA …”
Section: Discussionsupporting
confidence: 85%
“…DLQI scores for the week prior to presentation were higher in summer than in other seasons, indicating that large number of patients experienced poor quality of life. In other photodermatoses, there were many patients who had high DLQI scores and impairment of quality of life in the United States of America (USA) and the United Kingdom …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it is of interest to review a recent report of CAD, which included 29 patients, with median age at presentation of 40 years, who were of higher skin phototypes V and VI, as the majority had a history of atopic disease or preceding eczema of other type and photoexposed site dermatitis. 10 This again emphasizes the clear differences from our patient group, with respect to demographics and clinical characteristics.…”
Section: Polymorphic Light Eruption With Severe Abnormal Phototestingmentioning
confidence: 68%